Differential correlations of refractive error, axial length, and axial length-to-corneal curvature ratio with anterior segment biometrics in myopic refractive surgery candidates - Jian Zhang; Youlin Zhu; Ping Yuan; Xiaojuan Dong; Manyun Xie; Zongrui Ma; Rong Tian (Photodiagnosis and Photodynamic Therapy)
Purpose: To investigate the correlations of spherical equivalent (SE), axial length (AL), and AL to corneal curvature radius ratio (AL/CR) with anterior segment biometrics in candidates for myopic refractive surgery. Methods: Anterior segment biometrics of 2,478 myopic refractive surgery candidates measured by Pentacam were collected retrospectively. The anterior segment biometrics included anterior corneal curvature (ACC), posterior corneal curvature (PCC), white-to-white corneal diameter (WTW), central corneal thickness (CCT), corneal volume at 3 mm (CV), anterior corneal astigmatism (ACA), posterior corneal astigmatism (PCA), anterior corneal eccentricity (ACE), posterior corneal eccentricity (PCE), anterior corneal asphericity (ACAP), posterior corneal asphericity (PCAP), anterior chamber depth (ACD), and anterior chamber volume (ACV). The eyes were divided into four groups according to the AL: group 1, AL≤24 mm; group 2, 24mm<AL≤26 mm; group 3, 26mm<AL≤28 mm; group 4, AL≥28mm. The correlations between these biometrics with SE, AL, and AL/CR were assessed by Pearson or Spearman correlation tests. A correlation with a coefficient ≥0.3 and a p value <0.05 were considered significant. Results: In all AL groups, ACC was positively correlated with SE (r = 0.446 to 0.620) and negatively correlated with AL/CR (r = -0.704 to -0.894), whereas PCC was positively correlated with SE (r = 0.394 to 0.612) and negatively correlated with AL/CR (r = -0.606 to -0.787). WTW was positively correlated with SE (r = 0.304 to 0.474) in every group, and negatively correlated with AL/CR (r = -0.405 and -0.412) in group 1 and 4. ACA was positively correlated with AL (r = 0.310) and AL/CR (r = -0.333) in group 4. ACD was negatively correlated with AL (r = -0.304) in group 4, and positively correlated with AL/CR (r = -0.325) in group 2. ACV was positively correlated with SE (r = 0.344) in group 4, and positively correlated with AL (r = 0.303) in group 2. CCT, CV, PCA, ACE, PCE, ACAP, and PCAP was not significantly correlated with SE, AL, or AL/CR in any of group. Conclusions: Differential correlations were observed between anterior segment biometrics and SE, AL, and AL/CR, suggesting that various myopia indicators have different effects on ocular structures. These findings may help identify the ocular structures that can be targeted of refractive surgery.